2022
DOI: 10.3390/nu14112208
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Ulcerative Colitis in Mice by Sweet Tea (Lithocarpus litseifolius) via the Regulation of Gut Microbiota and Butyric-Acid-Mediated Anti-Inflammatory Signaling

Abstract: Sweet tea (Lithocarpus litseifolius [Hance] Chun) is a new resource for food raw materials, with plenty of health functions. This study aimed to investigate the preventive effect and potential mechanism of sweet tea extract (STE) against ulcerative colitis (UC). Briefly, BABL/c mice were treated with STE (100 and 400 mg/kg) for 2 weeks to prevent 3% dextran sulfate sodium (DSS)-induced UC. It was found that STE supplementation significantly prevented DSS-induced UC symptoms; suppressed the levels of pro-inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Supplementation of myricetin could effectively reverse gut dysbiosis that occurred in the HFD þ DSS group. Studies revealed that bacteria, such as Muribaculaceae (Mo et al, 2022), Lactobacillus (Rangan et al, 2019), Lachnospir-aceae_NK4A136_group (He et al, 2022), Blautia (Liu et al, 2021), Alistipes (Guo et al, 2021) were considered as beneficial bacteria in IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of myricetin could effectively reverse gut dysbiosis that occurred in the HFD þ DSS group. Studies revealed that bacteria, such as Muribaculaceae (Mo et al, 2022), Lactobacillus (Rangan et al, 2019), Lachnospir-aceae_NK4A136_group (He et al, 2022), Blautia (Liu et al, 2021), Alistipes (Guo et al, 2021) were considered as beneficial bacteria in IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Lachnospiraceae_NK4A136 group belongs to the family Lachnospiraceae and is a potentially beneficial bacterium associated with obesity. It is also related to the production of butyric acid ( 45 , 46 ). Ruminococcus play a crucial role in metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the abundance of Lactobacillus had a highly positive correlation with the SCFAs profiles while it had negative correlations with inflammatory factors, which were conducive to the suppression of intestinal inflammation. Lachnospiraceae_NK4A136_group is a kind of SCFAs−producing bacteria that promotes the biosynthesis of butyric acid [ 47 , 48 ]. We found that the abundance of the Lachnospiraceae_NK4A136_group was significantly increased in the DSS group, whereas its increase was also observed in the BUR groups.…”
Section: Discussionmentioning
confidence: 99%